2021
DOI: 10.1186/s12935-021-02356-2
|View full text |Cite
|
Sign up to set email alerts
|

CircTUBGCP3 facilitates the tumorigenesis of lung adenocarcinoma by sponging miR-885-3p

Abstract: Background Circular RNAs (circRNAs) act pivotal roles in the progression of multiple malignancies. However, the underlying mechanisms by which hsa_circ_0007031 (circTUBGCP3) contributes to lung adenocarcinoma (LAC) remain largely unknown. Methods The association of circTUBGCP3 expression with clinicopathological characteristics and prognosis in patients with LAC was determined by RT-qPCR and fluorescence in situ hybridization. The in vitro function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Knocking down circTUBGPC3 inhibited WNT10B expression while inhibiting miR-885-3p upregulated WNT10B in NCI-H460 cells. Overall, this study concluded that circTUBGPC3 promotes lung cancer progression by inhibiting miR-885-3p, thus allowing for the overexpression of WNT10B ( Yang Y. et al, 2021 ). Only one paper has investigated WNT10B in the progression of lung cancer, and further work should be carried out to elucidate the actions of WNT10B in normal lung cells, lung fibrosis, and lung cancer.…”
Section: Wnt10b and Cancermentioning
confidence: 71%
See 1 more Smart Citation
“…Knocking down circTUBGPC3 inhibited WNT10B expression while inhibiting miR-885-3p upregulated WNT10B in NCI-H460 cells. Overall, this study concluded that circTUBGPC3 promotes lung cancer progression by inhibiting miR-885-3p, thus allowing for the overexpression of WNT10B ( Yang Y. et al, 2021 ). Only one paper has investigated WNT10B in the progression of lung cancer, and further work should be carried out to elucidate the actions of WNT10B in normal lung cells, lung fibrosis, and lung cancer.…”
Section: Wnt10b and Cancermentioning
confidence: 71%
“…Furthermore, Yang et al (2021) reported that WNT10B was regulated by non-coding RNAs. Their study identified an overexpression of the circular RNA circTUBGPC3 in lung adenocarcinoma (LAC) patients ( Table 1 ), and high expression of circTUBGPC3 correlated with worse overall survival.…”
Section: Wnt10b and Cancermentioning
confidence: 99%
“…Another circRNA associated with LUAD is circTUBGCP3. Upregulation of this circRNA, or downregulation of miR-885-3p, was associated with pathological stage and poor survival in LUAD patients ( Yang et al, 2021 ). Mechanistically, sponging of miR-885-3p by circTUBGCP3 prevents the miRNA from suppressing cell proliferation and attenuated the tumor-promoting effects of circTUBGGCP3.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 99%
“…The vast majority of prognostic marker investigations in LC are based on the analysis of circRNA expression in tissues. A significant number of studies have been conducted on LUAD [ 195 , 196 , 197 , 198 , 199 ].…”
Section: Circrnas In Lcmentioning
confidence: 99%
“…circTUBGCP3 can act as a “sponge” for miR-885-3p, the role of which is to suppress cell proliferation and weaken the tumour-promoting effect of circTUBGCP3. Wnt10b, a target of miR-885-3p, may be upregulated by circTUBGCP3 and indicate poor survival in LC patients and points to the poor survival of patients with LC [ 198 ].…”
Section: Circrnas In Lcmentioning
confidence: 99%